Evaluation of The Athlete Development Program for Rowing in West Bandung Regency - Khaerani; Ruslan Rusmana; Dindin Bern Hardin (STKIP Pasundan Press, 2026)
This study aims to evaluate the rowing athlete development program in West Bandung Regency, particularly focusing on the canoeing team, using the CIPP (Context, Input, Process, and Product) evaluation model. This research applied a descriptive qualitative approach with data collection techniques including interviews, observation, documentation, and questionnaires. The evaluation results show that in the context aspect, there is strong community support and awareness of the importance of early athlete development. In the input aspect, the coach has adequate qualifications, but training equipment and facilities, such as boats and gym tools, remain insufficient. In the process aspect, training activities are well structured, but athlete participation is not yet optimal. In the product aspect, the development program has had a positive impact on athletes' physical, technical, and mental skills, as well as their discipline. The study concludes that the program is running fairly well but needs improvement, particularly in facility provision and increasing athlete engagement in training.